Upaya Meningkatkan Minat Belajar Anak Pada Masa Pandemi Melalui Bimbingan Belajar di Desa Perkebunan Bandar Selamat - Rismayani Rismayani; Zailani Zailani (Al-Ulum: Jurnal Pendidikan Islam, 2021)
The research aims to identify and obtain information about how important Bimbel is to increase children's interest in learning during a pandemic during the online learning process in schools. How is the influence of Bimbel on children's interest in learning during a pandemic during the online learning process? This study uses a qualitative descriptive approach, namely data analysis that emphasizes meaning, reasoning, definition of certain situations (in certain contexts) and describes what it is about the behavior of the object under study. Data collection tools are methods of observation, interviews and documentation. The method used is a direct approach through the observation method by observing directly during teaching mentoring activities. From the observation that tutoring is very effective as an effort to increase children's interest in learning during a pandemic during the online learning process, it can be seen where children are very enthusiastic in participating in these activities, besides that this tutoring can also help students who have difficulty in doing their homework. practice questions given from school.